Histone methyltransferase PRDM9 is not essential for meiosis in male mice - Mihola, Ondrej; Pratto, Florencia; Brick, Kevin; Linhartova, Eliska; Kobets, Tatyana; Flachs, Petr; Baker, Christopher L; Sedlacek, Radislav; Paigen, Kenneth; Petkov, Petko M; Camerini-Otero, R Daniel; Trachtulec, Zdenek (Genome research, 2019)
A hallmark of meiosis is the rearrangement of parental alleles to ensure genetic diversity in the gametes. These chromosome rearrangements are mediated by the repair of programmed DNA double-strand breaks (DSBs) as genetic crossovers between parental homologs. In mice, humans, and many other mammals, meiotic DSBs occur primarily at hotspots, determined by sequence-specific binding of the PRDM9 protein. Without PRDM9, meiotic DSBs occur near gene promoters and other functional sites. Studies in a limited number of mouse strains showed that functional PRDM9 is required to complete meiosis, but despite its apparent importance, Prdm9 has been repeatedly lost across many animal lineages. Both the reason for mouse sterility in the absence of PRDM9 and the mechanism by which Prdm9 can be lost remain unclear. Here, we explore whether mice can tolerate the loss of Prdm9 By generating Prdm9 functional knockouts in an array of genetic backgrounds, we observe a wide range of fertility phenotypes and ultimately demonstrate that PRDM9 is not required for completion of male meiosis. Although DSBs still form at a common subset of functional sites in all mice lacking PRDM9, meiotic outcomes differ substantially. We speculate that DSBs at functional sites are difficult to repair as a crossover and that by increasing the efficiency of crossover formation at these sites, genetic modifiers of recombination rates can allow for meiotic progression. This model implies that species with a sufficiently high recombination rate may lose Prdm9 yet remain fertile.
Keywords: histonlysin-N-methyltransferasa; Fertility; Male; Mice, Knockout; Histone-Lysine N-Methyltransferase; spermatogeneze; Meiosis; Spermatogenesis; mužské pohlaví; chromozom X; myši knockoutované; X Chromosome; fertilita; meióza; Animals; ženské pohlaví; zvířata; myši inbrední C57BL; myši; Mice, Inbred C57BL; Mice; Female